Integration of Islamic Thought and Scientific Knowledge in the Formation of Educational Institution Leadership - Adeoye, Moses Adeleke; Baharun, Hasan (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This research examines the urgent need for integrating Islamic thought with scientific knowledge within educational leadership, particularly in Islamic educational institutions. Employing a qualitative research design, the study identifies challenges and opportunities in implementing interdisciplinary curricula, proposes a comprehensive model of educational leadership, and provides practical implications for educators. Educational institutions can foster responsible citizenship and social responsibility by equipping students with the tools to navigate complex moral landscapes. Data were collected through interviews with educational leaders, revealing key challenges such as resistance to change, limited resources and systemic barriers. However, the findings highlight significant opportunities for enhancing student engagement and critical thinking through interdisciplinary approaches. The conclusions drawn from this study advocate for educational frameworks that promote academic excellence and foster ethical and moral development. This research contributes to the discourse on educational reform by offering actionable strategies for curriculum design, teacher training, and community collaboration. Ultimately, this work advocates for a holistic educational framework that aligns with Islamic values while responding to the demands of a globalised world.